Intention to Stay of Contract of Service Employees: Human Resource Management Policies and Practices, Organizational Support, Culture, And Work-Life Balance - Largo, Lady June (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the influence of human resource management (HRM) practices, perceived organizational support, organizational culture, and work–life balance on the intention to stay of Contract-of-Service (COS) faculty members at Tangub City Global College. The study was anchored on Job Embeddedness Theory, Strategic Human Resource Management, Organizational Support Theory, Cameron and Quinn’s Competing Values Framework of Organizational Culture, and the Work–Life Balance perspective. A quantitative approach employing descriptive-correlational and causal research designs was utilized. Data were collected from 111 Contract-of-Service faculty members through a modified survey questionnaire adapted from established instruments measuring the study variables. Descriptive statistics, Pearson Product-Moment Correlation, and multiple regression analysis were used to analyze the data. The findings revealed that HRM practices were generally effective, particularly in training, development, and employee involvement. Perceived organizational support was rated high, with supervisory and coworker support emerging as the strongest sources of support. Organizational culture was characterized by strong clan and market orientations, reflecting a balance of collaboration, innovation, and performance. Work–life balance was moderately high, with positive work–personal life enhancement outweighing work-related interference. The respondents also reported a high level of intention to stay, with coworker relationships, location, and socialization identified as the most influential factors. Significant relationships were found among HRM practices, perceived organizational support, organizational culture, work–life balance, and intention to stay. Regression analysis identified work–personal life enhancement as a positive predictor and coworker support as a significant predictor of intention to stay. The study concludes that non-monetary organizational factors play a vital role in sustaining employee commitment among Contract-of-Service faculty members. It recommends strengthening performance appraisal systems, institutional support mechanisms, recognition programs, work–life balance initiatives, and supportive workplace relationships to improve retention. This study supports SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice and Strong Institutions) by promoting workforce stability, supportive employment practices, and institutional effectiveness in higher education. Its sustainability contribution lies in providing evidence-based insights that can help local colleges strengthen employee retention, enhance organizational performance, and maintain the continuous delivery of quality educational services.
Keywords: Clan Culture; HRM Practices; Intention to Stay; Organizational Support; Work-Life Balance